PENGARUH TINGKAT KESEHATAN KEUANGAN TERHADAP JUMLAH KREDIT YANG DISALURKAN PADA PD.BPR BANK PASAR TEMANGGUNG - Yuanita Resti Astuti; Agus Hermani; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2013)
PD. BPR Bank Pasar Temanggung is one of the regional enterprises engaged in banking which carries on business as a Rural Bank in Temanggung maintain financial soundness by receiving funds from the public and distribute it in the form of loans. Credits provided by customers will help the bank in maintaining liquidity and the impact on interest income to be received so that it will affect the financial soundness of the bank. The research is motivated by use of financial statements in the time series in the last 4 years from 2008 to 2011. This study aims to determine the influence of the financial soundness CAMEL method to total loans in PD. BPR Bank Pasar Temanggung. The results showed that the healthcare finance on the amount of outstanding loan by 78,1% percent.